Synthesis of 4-aminomethyl-tetrahydrofuran-2-carboxylates with 2,4-cis and 2,4-trans relationships - Edwards, Alison A.; Sanjayan, Gangadhar J.; Hachisu, Shuji; Soengas, Raquel; Stewart, Alistair; Tranter, George E.; Fleet, George W. J. (Tetrahedron, 2006)
Templated tetrahydrofuran-based gamma-azido esters were prepared with the C-2 and C-4 functionalities in cis and trans relative configurations. This was achieved by ring contraction of the suitably protected 2-O-triflates of pentono-1,5-lactones (D-ribose and L-arabinose) with subsequent introduction of the azide via the 4-O-triflate. Access to a corresponding beta-azido ester was achieved in good yield. Little elimination product was observed by introduction of the azide via the 3-O-triflate. These azido esters are scaffolds. which may be predisposed to adopt secondary structural motifs, for example. for use as peptidomimetics; they may also be utilised for the preparation of stereodiverse compound libraries. (c) 2006 Elsevier Ltd All rights reserved.
Keywords: gamma amino acids; Peptidomimetics; scaffolds; sugar amino acids

Sequence-specific unusual (1 -> 2)-type helical turns in alpha/beta-hybrid peptides - Prabhakaran, Panchami; Kale, Sangram S.; Puranik, Vedavati G.; Rajamohanan, P. R.; Chetina, Olga; Howard, Judith A. K.; Hofmann, Hans-Joerg; Sanjayan, Gangadhar J. (Journal of the American Chemical Society, 2008)
This article describes novel conformationally ordered (alpha/beta-hybrid peptides consisting of repeating L-proline-anthranilic acid building blocks. These oligomers adopt a compact, right-handed helical architecture determined by the intrinsic conformational preferences of the individual amino acid residues. The striking feature of these oligomers is their ability to display an unusual periodic pseudo beta-turn network of nine-membered hydrogen-bonded rings formed in the forward direction of the sequence by 1–>2 amino acid interactions both in solid-state and in solution. Conformational investigations of several of these oligomers by single-crystal X-ray diffraction, solution-state NMR, and ab initio MO theory suggest that the characteristic steric and dihedral angle restraints exerted by proline are essential for stabilizing the unusual pseudo beta-turn network found in these oligomers. Replacing proline by the conformationally flexible analogue alanine (Ala) or by the conformationally more constrained alpha-amino isobutyric acid (Aib) had an adverse effect on the stabilization of this structural architecture. These findings increase the potential to design novel secondary structure elements profiting from the steric and dihedral angle constraints of the amino acid constituents and help to augment the conformational space available for synthetic oligomer design with diverse backbone structures.

Sheet-forming abiotic hetero foldamers - Baruah, Pranjal K.; Sreedevi, Naduthottiyil K.; Majumdar, Baisakhi; Pasricha, Renu; Poddar, Pankaj; Gonnade, Rajesh G.; Ravindranathan, Sapna; Sanjayan, Gangadhar J. (Chemical Communications, 2008)
Abiotic hetero oligomers, adopting a well-defined extended self-assembled sheet-like structure, derived from conformationally constrained aliphatic and aromatic amino acid residues repeating at regular intervals are reported.

Sterically controlled naphthalene homo-oligoamides with novel structural architectures - Prabhakaran, Panchami; Puranik, Vedavati G.; Chandran, Jima N.; Rajamohanan, P. R.; Hofmann, Hans-Joerg; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2009)
Herein we report novel naphthalene homo-oligoamides, derived from 4-amino-3-methoxy-naphthalene-2-carboxylic acid and 4-amino-1-methoxy-naphthalene-2-carboxylic acid as monomer building blocks, that display an anti-periplanar arrangement of the naphthyl rings, primarily induced by steric interactions between adjacent groups and functionalities.

Sugar-amino acid cyclic conjugates as novel conformationally constrained hydroxyethylamine transition-state isosteres - Roy, Arup; Sanjayan, Gangadhar J. (Tetrahedron Letters, 2012)
Hydroxyethylamine (HEA) isosteres have previously been shown to display a multitude of biomedical applications. In fact, the first protease inhibitor, saquinavir is an HEA based peptidomimetic. Herein we describe an easy-to-operate synthetic route to a series of carbohydrate-based conformationally constrained hydroxyethylamine (HEA) isosteres featuring amino acid side chains, starting from D-glucose. This class of novel sugar-amino acid-tethered conformationally restricted HEA systems may have bearing in practical application, particularly in the development of conformationally restricted protease inhibitors. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Conformationally constrained; D-Glucose; hydroxyethylamine isosteres; protease inhibitor; Reductive amination

Switching the H-bonding network of a foldamer by modulating the backbone chirality and constitutional ratio of amino acids - Ramesh, Veera V. E.; Vijayadas, Kuruppanthara N.; Dhokale, Snehal A.; Gonnade, Rajesh G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2013)
This communication describes the folding propensity of a hetero-foldamer motif featuring proline (Pro) and anthranilic acid (Ant) residues in a 1:2:1 (alpha: beta: alpha) constitutional ratio. Structural investigations unequivocally suggest that the hydrogen-bonding network of this foldamer motif can be switched between 9-membered and 6-membered by modulating the backbone chirality and constitutional ratio of the amino acid residues.

Synthetic zipper peptide motif orchestrated via co-operative interplay of hydrogen bonding, aromatic stacking, and backbone chirality - Nair, Roshna V.; Kheria, Sanjeev; Rayavarapu, Suresh; Kotmale, Amol S.; Jagadeesh, Bharatam; Gonnade, Rajesh G.; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Journal of the American Chemical Society, 2013)
Here, we report on a new class of synthetic zipper peptide which assumes its three-dimensional zipper-like structure via a co-operative interplay of hydrogen bonding, aromatic stacking, and backbone chirality. Structural studies carried out in both solid- and solution-state confirmed the zipper-like structural architecture assumed by the synthetic peptide which makes use of unusually remote inter-residual hydrogen-bonding and aromatic stacking interactions to attain its shape. The effect of chirality modulation and the extent of noncovalent forces in the structure stabilization have also been comprehensively explored via single-crystal X-ray diffraction and solution-state NMR studies. The results highlight the utility of noncovalent forces in engineering complex synthetic molecules with intriguing structural architectures.

Synthetic turn mimetics and hairpin nucleators: quo vadimus? - Nair, Roshna V.; Baravkar, Sachin B.; Ingole, Tukaram S.; Sanjayan, Gangadhar J. (Chemical Communications, 2014)
Structural mimicry of peptides has witnessed perceptible progress in the last three decades. Reverse turn and beta-hairpin units are the smallest secondary structural motifs that are some of the most scrutinized functional cores of peptides and proteins. The practice of mimicking, without altering the function of the bioactive core, ranges from conformational locking of the basic skeleton to total replacement of structural architecture using synthetic analogues. Development of heterogeneous backbones - using unnatural residues in place of natural ones - has broadened further opportunities for efficient structural rigidification. This feature article endeavours to trail the path of progress achieved hitherto and envisage the possibilities that lie ahead in the development of synthetic turn mimetics and hairpin nucleators.

Self-assembled vesicles of urea-tethered foldamers as hydrophobic drug carriers - Ingole, Tukaram S.; Kale, Sangram S.; Sukumaran, Santhosh Babu; Sanjayan, Gangadhar J. (Chemical Communications, 2016)
Molecular self-assembly of nonamphiphilic alpha,beta-hybrid foldamers based on urea-tethered anthranilic acid-proline (Ant-Pro) foldamers is reported. These self-assembled hollow vesicular architectures can take up and release the anticancer hydrophobic drug curcumin.

Structural insights into the hydrogen-bonding and folding pattern in ant-ant-pro-gly tetrapeptides - Baravkar, Sachin B.; Kotmale, Amol S.; Mobin, Samir R.; Gonnade, Rajesh Ghanshyam; Sanjayan, Gangadhar J. (European Journal of Organic Chemistry, 2017)
In this paper, we provide structural insights into the hydrogen-bonding and folding pattern in Ant-Ant-Pro-Gly tetrapeptides (Ant: anthranilic acid; Pro: proline; and Gly: glycine). Comparison of the C-terminal esters and their amide analogs revealed strikingly different H-bonding networks. Whereas the ester analogs displayed an open structure without terminal H-bonding interactions, the amide analogs showed a completely folded structure. Structural details were revealed by using a combination of X-ray crystal structure studies and NOE-based molecular dynamics (MD) simulation studies.

Synthesis and anticancer activity of conformationally constrained Smac mimetics containing pseudo beta turns - Baravkar, Sachin B.; Wagh, Mahendra A.; Paul, Debasish; Santra, Manas; Sanjayan, Gangadhar J. (Tetrahedron Letters, 2018)
Herein, we report synthesis and in vitro anticancer activity of conformationally constrained Smac mimetics containing reverse turn inducing motifs "Ant-Pro" and "sAnt-Pro". The synthesis of Smac analogs with diverse hydrophobic groups at the C-terminus was carried out using solution phase peptide synthesis. The synthesis of Ant-Pro containing analogs 3a-j was carried out by ring opening of benzoxazinones 7a-c, whereas, their sulfonamide counterparts 4a-h were synthesized by using routine acid-amine coupling reaction. In vitro anticancer studies against breast cancer cell line MDA-MB-231 revealed that some of the new analogs had better anticancer activity than the standard AVPI Smac tetrapeptide. (C) 2018 Published by Elsevier Ltd.

Synthesis and film formation of aqueous emulsion polymer latexes featuring hydrogen bonding via a janus guanine-cytosine base monomer - Thompson, Steven W.; Li, Joanna; Singh, Dharmendra; Sanjayan, Gangadhar J.; Zetterlund, Per B. (ACS APPLIED POLYMER MATERIALS, 2024)
Keywords: Emulsion polymerization; Film formation; Hydrogenbonding; Supramolecular networks